Decentralised state feedback control of multiagent systems using reduced-order functional observers. (12th June 2007) - Ha, Q.P.; Trinh, H.; Phat, V.N.
This paper presents a solution to the global state feedback control problem for multiagent systems under a complete decentralised information structure. The proposed solution is based on the design of reduced-order functional observers to estimate asymptotically the global control signals by using only the corresponding local output information subject to the condition of no information cross flows. New existence conditions for the reduced-order decentralised observers are derived and design procedures are presented. A numerical example is included for illustration.